Successful Surgical Intervention in An Unusual Case of Aspergillus Endocarditis with Acute Myeloid Leukemia - Zahra Ansari Aval; Seyed Mohsen Mirhosseini; Mohammad Fakhri; Amirhossein Mozaffary; Parisa Adimi Naghan; Neda Behzadnia; Zargham-Hossein Ahmadi (Acta Medica Iranica, 2013)
Endocarditis due to Aspergillus infection is a rare complication in patients with hematological malignancies. Here, we present a case of aspergillus endocarditis in a patient with acute myeloid leukemia (AML) successfully treated with antifungal therapy and surgical treatment. The patient was a 51 years old male, a known case of AML who was admitted to our medical center for evacuating his valvular vegetations and repairing his atrial septal defect. He underwent an open heart surgery to relinquish his thromboses and also received an antifungal regimen. The patient tolerated the procedure well and eight months after his surgery, the patient remains asymptomatic. Successful treatment of this severe case of aspergillus endocarditis justifies a multidisciplinary method to be as a safe and effective approach to manage these patients.